1983
DOI: 10.1159/000260715
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Phosphorus Content of Plaque and Saliva in Relation to Dental Caries

Abstract: Plaque and saliva samples were obtained from 55 children aged 13–15 years: 23 of them were caries free (group N) while the other 32 had evidence of high-caries activity over the preceding 2 years, with a mean DMFS of 25.9 (group H). The average concentration of calcium in posterior plaque of children in group N was 3.57 μg/mg (dry weight), compared with 1.63 μg/mg for group H. The average concentration of calcium in anterior plaque was 11.55 μg/mg in group N and 2.57 μg/mg in group H. The differences between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
9

Year Published

1990
1990
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 5 publications
7
46
0
9
Order By: Relevance
“…Entre estos últimos, existen componentes de naturaleza proteica de tipo inmunológico (IgA) o no (lisozima, lactoferrina, sialoperoxidasas, proteínas con actividad aglutinante y proteínas ricas en prolina, estaterina) cuyas concentraciones en la cavidad bucal podrían infl uir en la resistencia o susceptibilidad a la caries dental. 4 Respecto a los componentes salivales inorgánicos, Shaw et al 24 informaron la presencia de altas concentraciones de calcio (Ca) y fosfato (P) en sujetos libres ABSTRACT OBJECTIVE: To evaluate the association between saliva and prevalence of dental caries.…”
unclassified
“…Entre estos últimos, existen componentes de naturaleza proteica de tipo inmunológico (IgA) o no (lisozima, lactoferrina, sialoperoxidasas, proteínas con actividad aglutinante y proteínas ricas en prolina, estaterina) cuyas concentraciones en la cavidad bucal podrían infl uir en la resistencia o susceptibilidad a la caries dental. 4 Respecto a los componentes salivales inorgánicos, Shaw et al 24 informaron la presencia de altas concentraciones de calcio (Ca) y fosfato (P) en sujetos libres ABSTRACT OBJECTIVE: To evaluate the association between saliva and prevalence of dental caries.…”
unclassified
“…Kazein fosfopeptidin çoklu fosfoseril kalıntıları amorf kalsiyum fosfopeptide süpersature solusyonda bağla-narak faz transformasyonu için kritik boyuta ulaĢmasını önler. 45,46 Kazein fosfopeptid-amorf kalsiyum fosfatın antikaryojenik mekanizması nonokomplekslerin diĢ yüzeyindeki dental plakla birleĢip kalsiyum fosfat rezarvuarı olarak görev yapmasıyla açıklanabilir. Yapılan çalıĢmalarda kazein fosfopeptid-amorf kalsiyum fosfatın dental plakla birleĢmesinin plaktaki kalsiyum ve fosfat iyonlarının seviyesini arttırdığı gösterilmiĢtir.…”
Section: Cpp-acp ġçEren Ajanlarunclassified
“…Thus, the availability of calcium in plaque provides a natural anticaries protective effect, either by suppression of demineralization promoted by fermentative acids in mouth, through an increased remineralization by binding calcium ions to teeth enamel, or possibly a combination of both. An inverse relation between plaque calcium and caries incidence has been evidenced [124][125]. [126] has demonstrated that CPP-ACP can actually remineralize subsurface lesions in human enamel, and this is indeed the basis of one claim of his patent [127].…”
Section: Anticariogenic Effect Of Cpp In Yogurt and Cheesementioning
confidence: 99%